Entrepreneurship as a Career?: An Investigation of the Relationship Between Entrepreneurial Experience and Entrepreneurial Outcome - Rasmus Vendler Toft-Kehler (Copenhagen Business School (CBS), 2018)
Entrepreneurs and investors alike rely on prior entrepreneurial experience and talent as vital clues for anticipating entrepreneurial performance. However, the extent to which entrepreneurial expertise accumulates and the extent to which entrepreneurial talent can be defined and measured remain open for debate. Therefore, the studies of this dissertation have been conducted with the aim of advancing our understanding of how entrepreneurial experience and entrepreneurial talent relate to entrepreneurial performance and behavior. Each study offers insights into how entrepreneurial expertise accumulates and is therefore of relevance to multiple stakeholders
hdl:10398/9597
Keywords: 650